63 Let My People Sleep. (11th January 2018) - Brinkley, Genelle; Fox, Tiffani; McAfee, Lela; Fry, Jason; Young, Erlinda; Barnes, David; Quinn, Andrew; Balani, Jyoti; Sarode, Ravi; Lee, Francesca
Abstract: Objectives: Between 11 PM and 5 AM, the number of patients undergoing phlebotomy will be reduced by limiting collections to new admissions and STAT testing. Methods: (1) Ensure medical staff support in limiting testing overnight by presenting this concept to the medical executive committee. (2) Change the "Pre-rounds" order tab to reflect a start time of 5 AM, rather than 4 AM. (3) Clearly define the laboratory order priorities to minimize provider confusion. (4) Create a phlebotomist workflow to maximize specimen collection efficiency between 5 AM and 8 AM, allowing surgical and critical care floors to be collected first, general medical floors second, and geriatric and mother-baby floors last. (5) Perform real-time intervention with teams that continue to order overnight labs. (6) Make plans to create a "PM Rounds" order tab to allow a standardized evening draw schedule. (7) Make plans to assess timing of Q12, Q8, and Q6 hour draws to minimize need for overnight collection. Results: (1) Medical executive committee approval obtained; message sent to all medical staff stating that blood draws should not be ordered between 11 PM and 5 AM unless necessary. (2) Epic order tab changed to reflect the 5 AM start time for pre-rounds. (3) Epic lab orders include updated definition of routine, STAT, and timed . (4) Phlebotomist staffing and workflow maximized to allow efficient morning specimen collection. (5) Emails sent to attending providers of teams with unnecessary lab orders overnight for review. (6) In the first two weeks of this process, there was a 40% reduction in the number of patients who underwent phlebotomy between 11 PM and 5 AM. Conclusion: There is an increasing recognition of the importance of adequate, uninterrupted sleep in the hospital setting. With the positive outcome that we have seen in just two weeks, we project that we will see more satisfied patients and higher Press-Ganey scores.